Effect of 15-hydroxyprostaglandin dehydrogenase inhibitor on wound healing. (June 2015) - Seo, Seung Yong; Han, Song-Iy; Bae, Chun Sik; Cho, Hoon; Lim, Sung Chul
Abstract: PGE2 is an important mediator of wound healing. It is degraded and inactivated by 15-hydroxyprostaglandin dehydrogenase (15-PGDH). Various growth factors, type IV collagen, TIMP-2 and PGE2 are important mediators of inflammation involving wound healing. Overproduction of TGF- β and suppression of PGE2 are found in excessive wound scarring. If we make the condition downregulating growth factors and upregulating PGE2, the wound will have a positive effect which results in little scar formation after healing. TD88 is a 15-PGDH inhibitor based on thiazolinedione structure. We evaluated the effect of TD88 on wound healing. In 10 guinea pigs (4 control and 6 experimental groups), we made four 1 cm diameter-sized circular skin defects on each back. TD88 and vehicle were applicated on the wound twice a day for 4 days in the experimental and control groups, respectively. Tissue samples were harvested for qPCR and histomorphometric analyses on the 2nd and 4th day after treatment. Histomorphometric analysis showed significant reepithelization in the experimental group. qPCR analysis showed significant decrease of PDGF, CTGF and TIMP-2, but significant increase of type IV collagen in the experimental group. Taken together TD88 could be a good effector on wound healing, especially in the aspects of prevention of scarring.